2020
DOI: 10.3390/ma13235485
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Flax Tape-Reinforced Thermoset Composites

Abstract: Three thermoset resin systems—bio-epoxy, epoxy, and polyester-with 30 v% flax fiber reinforcement have been studied to identify the optimal fiber–resin combination in a typical composite structure. Tensile, interface and interlaminar shear strength together with flexural and impact damage tolerance were compared in this study. The results revealed that mechanical and interfacial properties were not significantly affected by the different resin systems. Microscopy studies reveal that epoxy laminates predominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Polyester resin was selected in this study due to the low cost, availability, and mechanical and water absorption properties comparable to those reported in a previous work. 40 γ-Radiation is not a new contribution of this work but was selected to check the secondary reinforcement effect on the mechanical performance of the composites. In this study, the constructed new dry fiber architecture woven preforms were achieved with a hand lay-up with polyester resin and further pressed in a compression molding machine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyester resin was selected in this study due to the low cost, availability, and mechanical and water absorption properties comparable to those reported in a previous work. 40 γ-Radiation is not a new contribution of this work but was selected to check the secondary reinforcement effect on the mechanical performance of the composites. In this study, the constructed new dry fiber architecture woven preforms were achieved with a hand lay-up with polyester resin and further pressed in a compression molding machine.…”
Section: Introductionmentioning
confidence: 99%
“…The main novelty of this work is based on the selection of the same yarn linear density for manufacturing woven types such as plain and twill derivatives (2/1 twill, 3/1 twill, a zigzag twill based on 2/2 twill, a diamond based on 2/2 twill) by using a conventional power loom weaving machine, only changing the drafting and denting plan to achieve the desired architecture of fabric and leaving the other weaving parameters the same. Polyester resin was selected in this study due to the low cost, availability, and mechanical and water absorption properties comparable to those reported in a previous work . γ-Radiation is not a new contribution of this work but was selected to check the secondary reinforcement effect on the mechanical performance of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major concerns surrounding the use of jute and other natural bres for composite applications is related to their lack of reinforcing abilities due to the poor tensile properties of dry bre architectures. 3 For example, woven, randomly oriented non-woven, and knitted structures generally involve yarn twisting, fabric crimping, and shorter bre lengths in nonwoven fabrics, adversely affecting the mechanical properties of jute bre composites. 4,5 Previous studies 2,5,6 have also suggested that the best mechanical properties can only be achieved in a composite if all the bres are printed in a parallel direction inside the composite.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] These natural fiber reinforced composites (NFRC) offer a range of benefits over their synthetic counter parts (glass, carbon, and Kevlar such as comparable specific mechanical properties, higher thermal stability, excellent damping properties, more environmentally friendly and cheap in price due to their natural abundance. [ 2–4 ] All of these fibers have almost similar morphologies, chemical compositions, and mechanical properties. However, their price and quality are determined based on the geographical locations/abundancy in the earth and also mode of uses (traditional or technical) in the produced country.…”
Section: Introductionmentioning
confidence: 99%
“…[2] To do that finding a novel jute fiber architecture (NJFA) is becoming a growing demand to the composites researchers in recent time. [2,4,7,8] Sarker et al [9] recently claimed a new jute fiber architecture with a unidirectional (UD) fiber arrangements which can offer maximum fiber packing capacity due to the individualization of the technical fiber by combination of combing chemical treatments. Though, relationship between the microdroplet and fiber from the NJFA is not yet fully understood.…”
mentioning
confidence: 99%